Vertical Distribution of Barnacle (Balanus sp) at Pier Pole of Sungai Bela Village Post in Indragiri Hilir Regency - Irvan Aditya Febrianto; Zulkifli '; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in october 2014, located in the port of Sungai BelaVillage in Indragiri Hilir of Riau Province. The aiem of the rescsrel was to study the verticaldistribution of barnacle (Balanus sp) at the pier pole. The methods used in this research wossurveying method The analysis of the density of barnacles (Balanus sp) showed differentbetween the number and the pillars of station I. The highest density was station I at themiddle part of the pole with the value of 142 individual/m2, and the lowest was in station II atthe top of the pole with the value of 71 individual/m2. The t-test results showed the average inabundance of barnacles on each station differed concrete with a value p = 0,19 (p>0,05)showing the different of a barnacle density in the top, middle, and bottom, respectively.Keywords : Sungai Bela, Barnacle (Balanus sp), Density, Indragiri Hilir, Pole pier.